Innovation in Reading Skills Assessment in Arabic Textbooks Based on HOTS Assessment - Amila Sholiha; R Umi Baroroh; Razita binti Abdullah (Izdihar : Journal of Arabic Language Teaching, Linguistics, and Literature, 2023)
The purpose of this scientific study was to analyse the HOTS-based test for assessment of reading skills and innovation in the Arabic textbook for grade XI published by the Ministry of Religious Affairs in 2020. This research used library research. The primary data source comes from an Arabic textbook, and the secondary data source comes from relevant research. The results of this study indicate that some of the assessments used in the grade XI Arabic textbook published by the Ministry of Religious Affairs have implemented tests at the HOTS cognitive level. In the textbook, there are 8 test items that fall into the realm of HOTS, containing 3 main test instruments, the rest of which only get repeated in the next chapter. This shows that there are still limited test instruments that contain the HOTS cognitive domains used in the textbook. In this study, there are 10 test instruments that contain the HOTS cognitive domain. Of the 10 test instruments given, there are 7 new ones, namely: finding the main idea, finding the message, finding the title, analysing relevant information, evaluating ideas, assessing the author's impression, and providing new ideas from the reading text. The innovation of this test instrument is explained with an overview of the implementation of each test instrument that contains the HOTS cognitive domain so that it can be understood and used for the development of Arabic reading skills test instruments.